Pembelajaran Tari Muli Siger Menggunakan Media Audio Visual di SMA Negeri 1 Sukoharjo - Andika Primartati; Agung Kurniawan; I Wayan Mustika; Susi Wendhaningsih (Jurnal Seni dan Pembelajaran, 2018)
The foccuss in this research is how the proccess is and the result after the Muli Sigegh teahcing learning through audio visual for eleventh grade students at SMAN 1 Sukoharjo. Constructivism theory was implemented in this research. Furthermore, qualitative descriptive was implemented as a design in tihs research. The population of this research was eleventh grade of senior high school students; where as five of students were chosen as the sample, and art teacher. The instruments were observation, documentation and interviewing the art teacher. The data were analyzed through data reduction. Serving the data, and drawing conclussion. The teaching leanring process of Muli Sigegh using audio visual, there were eight meeting of the implementation and most of the students could follow the teaching learning process well and also they got 76.28 as the average scores of the students.Permasalahan dalam penelitian ini adalah bagaimana proses pembelajaran tari muli siger menggunakan media audio visual. Teori yang digunakan adalah teori konstruktivisme. Penelitian ini merupakan penelitian deskriptif kualitatif. Sumber data yang diperoleh adalah siswa kelas XI IPS 4 yang berjumlah 5 siswa dan guru seni budaya. Teknik pengumpulan data yang digunakan adalah observasi, dokumentasi, dan wawancara yang dilakukan pada guru seni budaya. Analisis data penelitian ini adalah reduksi data, penyajian data, dan penarikan kesimpulan. Pada proses pembelajaran dilaksanakan selama delapan kali pertemuan, hasil yang diperoleh adalah siswa mampu mengikuti proses pembelajaran dan mendapatkan kriteria baik yaitu dengan skor 76,28 dan didukung media audio visual untuk tercapainya proses latihan yang baik dan maksimal.Kata kunci : Media Audio Visual, Pembelajaran, Tari Muli Siger.